OP12 Cumulative lifecourse adversity and adaptation in later life. (2nd September 2017) - Richardson, S; Sacker, A; Netuveli, G; Carr, E
Abstract : Background: Although exposures to cumulative socioeconomic disadvantage and adverse events over the lifecourse are associated with impaired physical and psychological health, the role of adverse events has received less attention. Furthermore, it is unclear to what extent their effects on later-life functioning depend on whether their primary harm was to the self or another person and their timing in the lifecourse, for example, during 'critical' or 'sensitive' periods. Methods: We used data on 5231 respondents aged 50+years over seven waves of the English Longitudinal Study of Ageing (2002–2015) to investigate adaptation in later life using cross-sectional CASP-12 scores, subjective life satisfaction and (CES-D) depression as outcomes. Cumulative lifecourse adversity was measured by counts of 16 types of adverse events occurring within five stages over the lifecourse (ages 0–5, 6–15, 15–30 and 31–50) using retrospective life history data. We fitted linear and logistic multilevel random intercept models in Stata 14 (for repeated observations nested within individuals) to evaluate the extent to which adverse events influence later life wellbeing and whether these associations differ according to self-versus-other orientation. Models were adjusted for labour market status, physical frailty score based on the cumulative deficit model, income, wealth and other household variables. Finally, we tested the association between cumulative adversity and trajectories of CASP-12 scores over time using a latent growth curve model. Results: CASP-12 scores were reduced by −0.49 (95% CI: −0.56 to −0.42) for each additional adverse event. This effect was similar for events occurring in each life stage and similar results were found for subjective life satisfaction and depression outcomes. Self-oriented events occurring in childhood had a greater (p<0.001) negative association (−0.62, 95% CI: −0.79 to −0.45) with later life wellbeing when compared with other-oriented events (−0.14, 95% CI: −0.32 to 0.03). Conversely, other-oriented events in adulthood exerted a greater influence. Total adverse life events were not associated with trajectories of CASP-12 by age. Conclusion: Adverse events occurring at all stages of the lifecourse were found to independently influence adaptation in later life. These age-dependent effects differed according to their self- or other-orientation, however. Our results support the theory of allostasis, in which previous exposure to stressors results in excessive allostatic load, susceptibility to future stressors, maladaptation and functional decline.